2015
DOI: 10.1371/journal.pone.0144160
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the Smell of Marijuana by Odor Impact of Volatile Compounds: An Application of Simultaneous Chemical and Sensory Analysis

Abstract: Recent US legislation permitting recreational use of marijuana in certain states brings the use of marijuana odor as probable cause for search and seizure to the forefront of forensic science, once again. This study showed the use of solid-phase microextraction with multidimensional gas chromatography—mass spectrometry and simultaneous human olfaction to characterize the total aroma of marijuana. The application of odor activity analysis offers an explanation as to why high volatile chemical concentration does… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
84
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(86 citation statements)
references
References 28 publications
0
84
0
2
Order By: Relevance
“…It also reflects the fact that many users select cannabis strains based on both the reported THC content and aroma (which is largely imparted by terpenoids; Gilbert and DiVerdi, 2018). A comprehensive analysis of cannabis strains recently indicated the presence of close to 200 detectable volatiles, which were tentatively identified based on searches against various spectral databases (Rice and Koziel, 2015). A notable challenge with terpenoid profiling pertains to the limitation that authentic standards are often very costly or unavailable from commercial sources, which is particularly true for sesquiterpenes (dozens detected by Rice and Koziel [2015]).…”
Section: Utility Of Metabolite Profiling For Strain Differentiationmentioning
confidence: 99%
See 1 more Smart Citation
“…It also reflects the fact that many users select cannabis strains based on both the reported THC content and aroma (which is largely imparted by terpenoids; Gilbert and DiVerdi, 2018). A comprehensive analysis of cannabis strains recently indicated the presence of close to 200 detectable volatiles, which were tentatively identified based on searches against various spectral databases (Rice and Koziel, 2015). A notable challenge with terpenoid profiling pertains to the limitation that authentic standards are often very costly or unavailable from commercial sources, which is particularly true for sesquiterpenes (dozens detected by Rice and Koziel [2015]).…”
Section: Utility Of Metabolite Profiling For Strain Differentiationmentioning
confidence: 99%
“…A comprehensive analysis of cannabis strains recently indicated the presence of close to 200 detectable volatiles, which were tentatively identified based on searches against various spectral databases (Rice and Koziel, 2015). A notable challenge with terpenoid profiling pertains to the limitation that authentic standards are often very costly or unavailable from commercial sources, which is particularly true for sesquiterpenes (dozens detected by Rice and Koziel [2015]). Commercial cannabis testing laboratories therefore rarely offer services that comprise more than 20 terpenoids.…”
Section: Utility Of Metabolite Profiling For Strain Differentiationmentioning
confidence: 99%
“…The contention that MB may not be the primary or sole signature odor of cocaine is supported by the studies of Rice and Koziel who reported that human odor detection thresholds for various VOCs associated with cocaine, heroin, and marijuana do not correlate with their headspace chemical concentrations. They propose that low concentrations of highly odorous compounds (i.e., very low odor detection thresholds) present in the headspace of these drugs may be primarily responsible for contributing to the overall odor of these drugs.…”
Section: Review and Analysis Of Scientific Literature On Canine Alertmentioning
confidence: 99%
“…Macias et al reported that detector dogs failed to alert to the dominant volatiles found in marijuana headspace. Concerning human olfactory detection of marijuana, Rice and Koziel have presented evidence that the odor of marijuana is probably not due to volatiles present in high concentration but rather highly odorous compound present in low concentration.…”
Section: Review and Analysis Of Scientific Literature On Canine Alertmentioning
confidence: 99%
“…The oxygenated compounds of the first fraction are commonly identified in most plant vapors [96] and are not particularly indicative of marijuana specifically. The sesquiterpene, β-caryophyllene, is usually found to be more concentrated and odorous than other compounds [105]. This can be seen in Figure headspace profile is shown in Figure 31A and Figure 31B.…”
Section: Resultsmentioning
confidence: 85%